Cardiopulmonary Cases - A Clinical Exam Skills E-Learning Module (Out of Print) - Jasna Jevtic; Dario Torre; James Sebastian (Association of American Medical Colleges, 2007)
Abstract Teaching physical exam skills to medical students is increasingly difficult as teachers face multiple barriers including patient recruitment issues, changing physical exam findings, and subjective assessments by different raters. Additionally, teaching the physical exam often still occurs in the lecture discussion and small-group model. We created this resource to improve the knowledge and skills of medical students in the cardiopulmonary physical exam, and assess their ability to accurately identify cardiac and pulmonary auscultory sounds by using an interactive e-module in the setting of limited teacher and patient resources. The module is accessible via the internet using the course management platform ANGEL. Once students log into ANGEL, the tutorial highlights cardiopulmonary physical exam psychomotor skills, physical exam findings, and relationship to pathophysiology. The tutorial features hyperlinks to physical exam skill videos and clinical skills websites. Subsequently, case-based lessons with video interviews, audio of normal and abnormal cardiac and pulmonary auscultory sounds, pictures of abnormal physical exam findings, and X-rays for individual cases are introduced. Students are asked to identify various physical exam findings and interpret abnormal sounds, as well as make a diagnosis during the case-based portion of the tutorial. There is a pre-/postcase-based quiz administered to assess students' cardiac and pulmonary auscultory knowledge, with cardiac and pulmonary sounds embedded within the quiz. This course was piloted with third-year preclerkship students with a mean score on the knowledge quiz of 61.6% (+/- 44%) prior to intervention, rising to 93.1% (+/- 19%) after the web-based curriculum. Seventy percent of students rated the web-based module as very good or excellent. Program evaluation by students averaged > 4.0 (1 = strongly disagree, 5 = strongly agree) for satisfaction with the curriculum in helping identify abnormal cardiac and pulmonary auscultory sounds. Qualitative data indicated that medical students felt the web hyperlinks, cases, graphics, video, and audio files enhanced their learning experience. They described ease of accessibility and flexibility as key favorable components of the module.